profil Profiles of science process skills and sustainability awareness of junior high school students: Profiles of science process skills and sustainability awareness of junior high school students - Sifah, Layyinatus; Dewi, Endah Rita Sulistya; Roshayanti, Fenny; Hayat , Muhammad Syaipul (UNIB Press, 2024)
The 21st century require students to have skills in solving everyday problems as well as sustainability awareness. This awareness includes understanding, attitudes, and actions that support efforts to preserve the environment and sustainable development. The purpose of this study was to determine the profile of science process skills and sustainability awareness in students' ESD concepts. The method used in this research is descriptive. The samples in this study were students of class VIII B SMP Negeri 23 Semarang. The instruments used were multiple choice questions to measure the level of science process skills and questionnaires to determine students' sustainability awareness. The results showed that students' science process skills were still at a sufficient level with an average percentage of 61.97, while the percentage level of students' sustainability awareness was in the medium category with a percentage of 66.2. So it can be concluded that in science learning, there is a need for the science process skills approach and the application of problem-based learning models integrated with ESD in an effort to improve the science process skills and sustainability awareness of junior high school students. The demands of the 21st century require students to have skills in solving everyday problems and sustainability awareness. This awareness includes understanding, attitudes, and actions that support environmental conservation and sustainable development.